2015
DOI: 10.1186/s12871-015-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

Optimal pain management for radical prostatectomy surgery: what is the evidence?

Abstract: BackgroundIncrease in the diagnosis of prostate cancer has increased the incidence of radical prostatectomy. However, the literature assessing pain therapy for this procedure has not been systematically evaluated. Thus, optimal pain therapy for patients undergoing radical prostatectomy remains controversial.MethodsMedline, Embase, and Cochrane Central Register of Controlled Trials were searched for studies assessing the effects of analgesic and anesthetic interventions on pain after radical prostatectomy. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 61 publications
0
32
0
4
Order By: Relevance
“…The authors of this meta-analysis also established that the cumulative opioid-sparing effect of the TAP block was 11 mg after 24 h, which they qualified marginal and of questionable clinical relevance. 13 There is no gold standard technique that could have been used as a positive control in this setting. Another recent randomized controlled trial showed that dual transversus abdominis plane block reduced pain scores upon sitting after laparoscopic appendectomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors of this meta-analysis also established that the cumulative opioid-sparing effect of the TAP block was 11 mg after 24 h, which they qualified marginal and of questionable clinical relevance. 13 There is no gold standard technique that could have been used as a positive control in this setting. Another recent randomized controlled trial showed that dual transversus abdominis plane block reduced pain scores upon sitting after laparoscopic appendectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of effect is in agreement with the little evidence supporting the efficacy of TAP block or intravenous lignocaine for open prostatectomy despite their widespread use. 13 There is no gold standard technique that could have been used as a positive control in this setting. In particular, epidural analgesia was considered but rejected because the risk-benefit ratio was deemed unfavourable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En cirugía urológica y ginecológica abierta, con incisiones infraumbilicales o lumbotomías, con estancias hospitalarias cortas y bajas demandas analgésicas, tampoco se recomienda la analgesia epidural, que produciría más riesgos que beneficios (12,13). En la nefrectomía y el implante renal, el bloqueo TAP proporciona una buena analgesia postoperatoria, disminuyendo el consumo de opioides (14).…”
Section:  Los Programas De Recuperación Intensificada (Enhanced Recounclassified